Songs and rhymes in primary school - Novák Lászlóné (2002)
In this thesis I try to show the important role of rhymes and songs and the way how they make the language learning process more interesting and enjoyable to primary school students. Besides, they encourage and make pupils desperate to learn language as efficiently as possible. Since my first graduation I have been dealing with the motivation of pupils providing by rhymes and songs. They are, of course, not the only things that enough to improve their language knowledge, but they develop their ability of thinking, studying, using understanding the English language. In my dissertation I prove with my research how English songs and rhymes could help students in their efforts of language learning and how they could make the atmosphere more relaxing and effective.